The protein ontology project: Structured vocabularies for proteins - Chang, Elizabeth; Sidhu, Amandeep; Sidhu, B.; Dillon, Tharam S. (WIT Press, 2005)
The rapid generation of accessible protein data sources has generated confusion over protein data representation. The protein ontology project seeks to provide a set of structured vocabularies for protein domains that can be used to describe cellular products in any organism. The work includes modelling protein structure and experimental data. The protein ontology framework describes: (1) Protein sequence and structure information, (2) Protein folding process, (3) Cellular functions of proteins, (4) Molecular bindings internal and external to Proteins and (5) External factors affecting final protein conformation. In this paper we will also discuss the implementation strategy for the protein ontology project. The protein ontology project provides a community resource using these, vocabularies promoting the use of common protein data representation. The goal of the protein ontology project is to produce a dynamic, controlled data and query vocabulary that can be applied to all proteins even as the knowledge of protein roles in cells is accumulating and changing.